Special paperDry skin as an up-to-date clinical problem - Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Research into the structure and function of the stratum corneum has increased substantially over the past two decades. Therefore our understanding of the role of desquamatory process in the normal functioning of the skin has also increased. Perturbation of the desquamatory process leads to dry skin regardless the cause. The dry skin condition has been shown to be largely due to the inhibition of corneodesmosomal degradative process, with the resultant retention of these binding complexes in the superficial layers of stratum corneum. The underlying cause appears to be loss of water from the tissue due to perturbations of one or both of the systems which are primarily responsible for maintaining stratum corneum water content; namely NMF and barrier lipids. The most effective treatment for the dry skin is moisturization with either traditional occlusive agents or humectants or new methodologies. Moisturizing agents, which supplement the barrier lipids, either by direct application or by increasing intrinsic lipogenesis are becoming available. In addition enhancing corneodesmosomal degradation provides new fields for novel moisturizing products. Contemporary patients expect dermatologists and pharmacists to be able to recommend treatment for various dry skin conditions upon evidence-based medicine. Key words: dry skin, ceramides, natural moisturizer factor.